The new potato. Breeders seek a breakthrough to help farmers facing an uncertain future - Stokstad, E. (American Association for the Advancement of Science, 2019)
Potato is the important food crop after wheat and rice, and its nutritious tubers are becoming increasingly popular in the developing world. Keeping up with the demand means adapting the potato to thrive in various soils and climates. It must also resist new threats from pests, disease, heat, and drought. Creating a new potato variety is slow and difficult, but there are new approaches, including genetic engineering. Potato breeders are particularly excited about hybrid diploid breeding, a method that could cut the time required to create new varieties by more than half, make it easier for breeders to combine traits in one variety, and allow farmers to plant seeds instead of bulky chunks of tuber. In addition, breeders will soon have more genetic diversity available to improve cultivated potatoes. Plant collectors are finishing a big effort to find and conserve the hardy wild relatives of potato, which have traits that could make the crop more robust and resilient.